Effects of Duloxetine Treatment on Cognitive Flexibility and BDNF Expression in the mPFC of Adult Male Mice Exposed to Social Stress during Adolescence - Xu, Hang; Zhang, Yu; Zhang, Fan; Yuan, San-na; Shao, Feng; Wang, Weiwen (Frontiers in Molecular Neuroscience, 2016)
Early stress is a significant risk factor for the onset of mood disorders such as depression during adulthood. Impairments in cognitive flexibility mediated by prefrontal cortex (PFC) dysfunction are increasingly recognized as important etiological and pathological factors in the development of depression. Our previous study demonstrated that social defeat stress during early adolescence produced delayed deficits in cognitive flexibility in adult mice. The potential molecular mechanisms underlying these long-term consequences remain unclear. One candidate molecule is brain-derived neurotrophic factor (BDNF), which plays a vital role in neural development and synaptic plasticity. In this study, we initially examined the effects of adolescent social stress on cognitive flexibility and PFC BDNF expression within a week after the last stress exposure and 6 weeks later during adulthood. Adolescent (PND 28) male mice were subjected to stress or control manipulation for 10 days. The attentional set-shifting task (AST) was used to assess cognitive flexibility. Levels of BDNF mRNA and protein in the PFC were examined after behavioral testing. The results demonstrated that previously stressed mice exhibited delayed extra-dimensional set-shifting deficits in AST when tested as adults but not when tested as adolescents. Consistent with the cognitive alterations, adolescent stress induced dynamic alterations in BDNF expression in the medial PFC (mPFC), with a transient increase observed shortly after the stress, followed by a decrease 6 weeks later during adulthood. Next, we further determined the effects of chronic treatment with the antidepressant duloxetine during early adulthood on cognitive and molecular alterations induced by adolescent stress. Compared with the controls, duloxetine treatment reversed the cognitive deficits and increased the BDNF protein expression in the mPFC during adulthood in previously stressed mice. These findings demonstrated that BDNF expression in the mPFC was sensitive to adolescent social stress, which may contribute to the disturbance of the development and later functioning of this brain region.